Agente pedagógico para mediação do processo de ensino-aprendizagem da dedução natural na lógica - Galafassi, Fabiane Flores Penteado (Universidade do Vale do Rio dos Sinos, 2012)
Logic is a mathematical science of nature that is strongly linked to Philosophy, tending the laws of reasoning, or right thinking, therefore, an instrument of thought. So learning the logic is necessary to ensure that our thoughts are carried correctly to produce true knowledge. Logic studies the methods and principles used to distinguish correct from incorrect reasoning. Thus, the logic is a fundamental discipline for academic courses of Computer Science. However, the persistence of high levels of premature failure or dropouts shows that there is ample room for improving the process of teaching this subject. In this context, a particularly critical of Logic and causing severe difficulties for students is learning the processes of formal deduction. With this question in mind, this paper aims to propose a computational model of mediation appropriate for the teaching of Natural Deduction for Propositional Logic, incorporated as a pedagogical agent to assist students in their learning process, serving as a tool support for this process. This agent is part of a research project, named Heraclitus, which aims to integrate and apply the technologies of Smart Objects Learning and Pedagogical Agents in teaching Logic.
Keywords: Objetos de aprendizagem; Sistemas tutores inteligentes; Agentes pedagógicos; Estratégias de mediação; Learning objects; Virtual learning environments; Intelligent tutoring systems; Software agents; Mediation learning; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação